NILAI STATUS DAN PERUBAHAN KESEHATAN HUTAN MANGROVE (STUDI KASUS HUTAN MANGROVE DI DESA MARGASARI, KECAMATAN LABUHAN MARINGGAI, KABUPATEN LAMPUNG TIMUR): The Value of Status and Changes in Mangrove Forest Health (Case Study in Margasari Village, Labuhan Maringgai District, East Lampung Regency) - Rahmat Safe'i (PERENNIAL, 2020)
he mangrove forest in Margasari Village, Labuhan Maringgai District, East Lampung Regency is a mangrove forest ecosystem that holds a lot of potential, both physically, economically and ecologically. Therefore, the condition of the mangrove forest ecosystem must remain sustainable. Regular forest health monitoring can support the achievement of sustainable forest management, thereby ensuring the quality and quantity of forests. This study aims to determine the status and health changes of mangrove forests in Margasari Village, Labuhan Maringgai District, East Lampung Regency. The first measurement was carried out in March 2019 and the second in March 2020 which is located in the mangrove forest of Margasari Village, Labuhan Maringgai District, East Lampung Regency. The stages of this research were the determination of cluster plots, making cluster plots, measuring forest health, processing and analyzing data, and assessing the health of mangrove forests, using the Forest Health Monitoring (FHM) method. The first measurement results obtained 50% "good" and "bad" status, while the second measurement results obtained 25% "medium" and "good" status and 50% "bad" status. Thus, there was a change in the value of the health condition of the mangrove forest in Margasari Village which tended to be quite unfavorable.